2016
DOI: 10.1021/acs.jmedchem.6b00527
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of New Chemical Entities for Old Targets: Insights on the Lead Optimization of Chromone-Based Monoamine Oxidase B (MAO-B) Inhibitors

Abstract: The discovery of new chemical entities endowed with potent, selective, and reversible monoamine oxidase B inhibitory activity is a clinically relevant subject. Therefore, a small library of chromone derivatives was synthesized and screened toward human monoamine oxidase isoforms (hMAO-A and hMAO-B). The structure-activity relationships studies strengthen the importance of the amide spacer and the direct linkage of carbonyl group to the γ-pyrone ring, along with the presence of meta and para substituents in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 34 publications
3
98
1
1
Order By: Relevance
“…On the other hand, substitution with fluorine produced a less potent MAO‐B inhibitor than chlorine and bromine substituents in both series of chalcones. Properties such as atomic radius and/or electronegativity may therefore play a significant role in the ligand–enzyme interaction …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, substitution with fluorine produced a less potent MAO‐B inhibitor than chlorine and bromine substituents in both series of chalcones. Properties such as atomic radius and/or electronegativity may therefore play a significant role in the ligand–enzyme interaction …”
Section: Figurementioning
confidence: 99%
“…Properties such as atomicr adius and/ or electronegativity may therefore play as ignificantr ole in the ligand-enzymei nteraction. [38] Electron-donating substituents such as ethyl and methoxy groups in chlorine-containingc halcones have as ignificant influence on hMAO-B inhibition;f or example, compounds P16 and P13 were found to be better in terms of potency and selectivity than the corresponding compounds P1 and P11 without these substituents. In particular,m ethoxy-substituted compound P13 showedaK i value of 0.22 AE 0.01 mm with SI = 37.55; this SI is much highert han that of the standard selegiline.…”
mentioning
confidence: 99%
“…Reis et al reported screening of new library of chromone derivatives toward inhibition of hMAO‐B (Figure ). The compounds were found to potent inhibitors in nanomolar to picomolar concentration range and were highly selective for MAO‐B.…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
“…Chromones ( 54a ‐ b ) . hMAO, human monoamine oxidase; IC 50 , half maximal inhibitory concentration; SI, selectivity index…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
“…[3][4][5] Recently, several research groups have reported chromone derivatives substituted at different positions of the chromone ring and their inhibitory effects towards MAO-A and MAO-B. 2,[6][7][8][9][10][11][12] These reports suggested that structural changes induced by the substitutions on the chromone ring can increase the biological activity of the compound.…”
mentioning
confidence: 99%